The Speech-to-Song Illusion Is Reduced in Speakers of Tonal (vs. Non-Tonal) Languages - Jaisin, Kankamol; Suphanchaimat, Rapeepong; Figueroa Candia, Mauricio A.; Warren, Jason D. (Frontiers in Psychology, 2016)
The speech-to-song illusion has attracted interest as a probe of the perceptual interface between language and music. One might anticipate differential speech-to-song effects in tonal versus non-tonal languages, since these language classes differ importantly in the linguistic value they assign to tones. Here we addressed this issue for the first time in a cohort of 20 healthy younger adults whose native language was either tonal (Thai, Mandarin) or non-tonal (German, Italian) and all of whom were fluent in English. All participants were assessed using a protocol designed to induce the speech-to-song illusion on speech excerpts presented in each of the five study languages. Over the combined participant group, there was evidence of a speech-to-song illusion effect for all language stimuli and the extent to which individual participants rated stimuli as ‘song-like’ at baseline was significantly positively correlated with the strength of the speech-to-song effect. However, tonal and non-tonal language stimuli elicited comparable speech-to-song effects and no acoustic language parameter was found to predict the effect. Examining the effect of the listener’s native language, tonal language native speakers experienced significantly weaker speech-to-song effects than non-tonal native speakers across languages. Both non-tonal native language and inability to understand the stimulus language significantly predicted the speech-to-song illusion. These findings together suggest that relative propensity to perceive prosodic structures as inherently linguistic versus musical may modulate the speech-to-song illusion.